Jonathan Sacks : universalizing particularity - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2013)
This volume features the thought and writings of Jonathan Sacks, one of today's leading Jewish public thinkers. It brings together an intellectual portrait, four of his most original and influential philosophical essays, and an interview with him. This volume showcases the work of Sacks, a philosopher who seeks to confront and offer solutions to the numerous problems besetting Judaism and its confrontation with modernity. In addition, the reader will also encounter an important social philosopher and proponent of interfaith dialogue, who articulates how it is possible to cultivate a culture of civility based on the twin notions of the dignity of difference and the ethic of responsibility. Jonathan Sacks has been Chief Rabbi of the United Hebrew Congregations of the Commonwealth from September 1991 to September 2013 and a member of the House of Lords since 2009.